Editor’s Highlight: Collaborative Cross Mouse Population Enables Refinements to Characterization of the Variability in Toxicokinetics of Trichloroethylene and Provides Genetic Evidence for the Role of PPAR Pathway in Its Oxidative Metabolism - Venkatratnam, Abhishek (Toxicol Sci, 2017)
BACKGROUND: Trichloroethylene (TCE) is a known carcinogen in humans and rodents. Previous studies of inter-strain variability in TCE metabolism were conducted in multi-strain panels of classical inbred mice with limited genetic diversity to identify gene-environment interactions associated with chemical exposure. OBJECTIVES: To evaluate inter-strain variability in TCE metabolism and identify genetic determinants that are associated with TCE metabolism and effects using Collaborative Cross (CC), a large panel of genetically diverse strains of mice. METHODS: We administered a single oral dose of 0, 24, 80, 240, or 800 mg/kg of TCE to mice from 50 CC strains, and collected organs 24 h post-dosing. Levels of trichloroacetic acid (TCA), a major oxidative metabolite of TCE were measured in multiple tissues. Protein expression and activity levels of TCE-metabolizing enzymes were evaluated in the liver. Liver transcript levels of known genes perturbed by TCE exposure were also quantified. Genetic association mapping was performed on the acquired phenotypes. RESULTS: TCA levels varied in a dose- and strain-dependent manner in liver, kidney, and serum. The variability in TCA levels among strains did not correlate with expression or activity of a number of enzymes known to be involved in TCE oxidation. Peroxisome proliferator-activated receptor alpha (PPARα)—responsive genes were found to be associated with strain-specific differences in TCE metabolism. CONCLUSIONS: This study shows that CC mouse population is a valuable tool to quantitatively evaluate inter-individual variability in chemical metabolism and to identify genes and pathways that may underpin population differences.